THE USE OF BIGBOOK IN DEVELOPING Autistic STUDENTS' ALOUD READING SKILLS - Nurfaidah Nurfaidah; Yantoro Yantoro; Destrinelli Destrinelli (Jurnal Mantik, 2022)
This research was conducted at State Elementary School 131/IV Jambi City in the even semester of the 2021/2022 academic year. This research method is descriptive qualitative using data collection techniques in the form of interviews, observations and documents.From the results of the study it can be concluded that the use of. Big Book influences the development of aloud reading skills of mild autistic students through shared reading activities focusing on vocabulary.  It is worth trying out in the learning process because it is included in the category of attractive media with its appearance which is dominated by images and large and colorful text sizes. It is recommended that teachers can use the Big Book media in appropriate learning materials. Meanwhile, data analysis was carried out by collecting data, reducing data, presenting data and drawing conclusions. From the results of the study it can be concluded that the use of. Big Book influences the development of aloud reading skills of mild autistic students through shared reading activities focusing on vocabulary. It is worth trying out in the learning process because it is included in the category of attractive media with its appearance which is dominated by images and large and colorful text sizes. It is recommended that teachers can use the Big Book media in appropriate learning materials.